2014
DOI: 10.1016/j.watres.2014.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characterisation of thermally-treated anaerobic digested sludge: Impact of temperature and thermal history

Abstract: This study investigated the partially irreversible effect of thermal treatment on the rheology of digested sludge when it was subjected to temperature change between 20 °C and 80 °C and then cooled down to 20 °C. The yield stress, infinite viscosity and liquor viscosity of sludge were measured at 20 °C for different thermal histories and were compared to the evolution of the solubilised chemical oxygen demand (COD) of sludge liquor. The results showed that thermal history irreversibly affects sludge rheology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…1). Similarly, Farno et al [30] found that the increase in the level of solubility induces that some particulate organic matter inside the sludge changed their phase and solubilised into liquid medium (interstitial liquid), thus increasing the viscosity of liquid medium. Thus, the bulk solutions of treated sludges are more complex fluids comprised of EPSs, Table 3 Capillary suction time, Ostwald-de Waele parameters and water removed by centrifugation of untreated and treated sludge samples.…”
Section: Molecular Weight Distributions Of the Eps Fractionsmentioning
confidence: 92%
“…1). Similarly, Farno et al [30] found that the increase in the level of solubility induces that some particulate organic matter inside the sludge changed their phase and solubilised into liquid medium (interstitial liquid), thus increasing the viscosity of liquid medium. Thus, the bulk solutions of treated sludges are more complex fluids comprised of EPSs, Table 3 Capillary suction time, Ostwald-de Waele parameters and water removed by centrifugation of untreated and treated sludge samples.…”
Section: Molecular Weight Distributions Of the Eps Fractionsmentioning
confidence: 92%
“…Solubilisation of COD due thermal treatment is also an indication of structural change in sludge after thermal treatment. Farno et al (2014) [8] showed that sludge which was treated at 50-80°C and then cooled down to 20°C contained higher soluble COD compared to the untreated sludge at 20°C. This can be because of irreversible destructing bonds in sludge during the thermal treatment.…”
Section: Strain Sweep Testmentioning
confidence: 99%
“…Literature survey suggests that thermal treatment of sludge (digested or WAS) at 50-80°C results in modification of sludge rheological properties such as yield stress and apparent viscosity [7]. Farno et al (2014Farno et al ( , 2015 and 2016) [7][8][9] showed that the yield stress and the apparent viscosity of digested sludge and WAS reduced by increasing thermal treatment temperature and its duration and there is a linear relationship between thermally-induced compositional change of sludge indicated by soluble COD and the decrease in yield stress and infinite viscosity. They proved that the compositional changes of sludge (i.e.…”
mentioning
confidence: 99%
“…Similar results were reported by Bougrier et al [35], who found that the CST value increased at low temperatures and decreased at temperatures higher than 130°C. Farno et al [36] found that the increase of soluble chemical oxygen demand (COD) with temperature of thermal history (up to 80°C) was linearly proportional to the increase in viscosity of the liquid medium of the sludge. This could possibly explain the increased CST value at temperatures below 100°C.…”
Section: Resultsmentioning
confidence: 99%